A first principles study on newly proposed (Ca/Sr/Ba)Fe2Bi2 compounds with their parent compounds. Issue 5 (11th February 2016) - Sundareswari, M.; Jayalakshmi, D. S.; Viswanathan, E.
Abstract: The structural, electronic, bonding and magnetic properties of newly proposed iron-based compounds viz., CaFe2 Bi2, SrFe2 Bi2, BaFe2 Bi2 with their Fermi surface topology are reported here for the first time by means of first principles calculation. All these properties of newly proposed compounds are compared and analysed along with their respective parent compounds namely (Ca, Sr, Ba)Fe2 As2 .